Phenotypes performance of tilapia best, nirwana II, jatimbulan, and sultana using floating net, and pond culture system - Ibrahim Satrio Faqih; Dinar Tri Soelistyowati; Odang Carman (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2015)
Tilapia is one of the introduced fish species in Indonesia and was firstly imported from Taiwan in 1969. Since that time, many efforts have been made to increase its quality through genetic improvement. Some strains of tilapia have been successfully generated such as best, nirwana II, jatimbulan and sultana. In sustainable aquaculture, success of culture production depends on good environmental conditions and water quality. The aim of this study was to evaluate the phenotype performances of four strains of tilapia obtained through selective breeding reared in floating net and ponds. A completely randomized designs with two factors were used in this research, i.e. strains of tilapia and culture system with three replicates. Fifty fish with an average body length of 3-5 cm was reared in ponds and floating net 2 x 2 x 1 m, fed daily in the morning and afternoon during the experiment. Twenty fish from each strain were sampled in every two weeks and fish body length and body weight were measured. Truss morphometric measurement was conducted after 12 weeks of rearing process. The results showed that sultana strain has the highest growth rate, jatimbulan and best strains have the similar survival and feed conversion rates, while the highest biomass was found in the best strain. The nirwana II has the lowest survival rate (18%), but this strain showed the highest feed efficiency. Culture system affects the phe-noltypic variance of truss morphometric, viz. eleven characters in floating net and two characters in pond specimens. Abstrak Nila di Indonesia merupakan ikan introduksi yang didatangkan dari Taiwan pertama kali pada tahun 1969. Dalam peri-ode yang cukup lama, upaya peningkatan kualitas benih ikan dilakukan secara terus menerus melalui perbaikan mutu genetik. Beberapa strain ikan nila yang telah dihasilkan di antaranya nila best, nirwana II, jatimbulan, dan sultana. Da-lam kegiatan perikanan budi daya yang berkelanjutan, faktor lingkungan dan kualitas perairan merupakan pembatas ke-berhasilan usaha budi daya. Tujuan penelitian ini adalah untuk mengevaluasi keragaan fenotipe empat strain ikan nila hasil pemuliaan pada sistem budi daya karamba jaring apung (KJA) dan kolam air tenang. Penelitian ini dirancang menggunakan rancangan acak lengkap pola faktorial yang terdiri atas faktor empat strain ikan nila dan faktor sistem bu-di daya yaitu KJA dan kolam air tenang. Setiap perlakuan diulang tiga kali. Tiap wadah kolam dan KJA ber-ukuran 2 x 2 x 1 m3 dimasukkan benih sebanyak 50 ekor berukuran 3-5 cm, dan diberi pakan pada pagi dan sore selama masa pe-meliharaan. Setiap dua minggu dilakukan sampling masing-masing strain 20 ekor untuk pengamatan panjang dan bo-bot. Setelah 12 minggu pemeliharaan dilakukan pengukuran truss morfometrik. Hasil penelitian menunjukkan bahwa ikan nila strain sultana memiliki laju pertumbuhan tertinggi, jatimbulan memiliki tingkat kelangsungan hidup dan kon-versi pakan yang sama dengan best, biomassa tertinggi dicapai pada nila best, sementara nirwana II memiliki kelang-sungan hidup yang paling rendah (18%) namun memiliki efisiensi pakan yang terbaik. Sistem pemeliharaan memenga-ruhi peningkatan ragam fenotipe truss morfometrik yakni 11 karakter di KJA dan dua karakter di kolam air tenang.